Sprawowanie Eucharystii poza miejscem świętym - Janczewski, Zbigniew (Prawo Kanoniczne, 2009)
The Eucharistic celebration is to be carried out in a sacred place. Unless in a particular cases necessity requires otherwise, in a fitting places (can. 932). The first, this article discusses the history of Eucharistic celebrations beyond a sacred places. The second it discusses modern canon law about those questions. The author shows the problem of necessity to celebration. In the Code of Canon Law 1983 arise of necessity appreciated a celebrants. Now according to Instruction Redemptionis sacramentum (25 march 2004) arise of necessity appreciates a diocesan bishop. The article show a various possibilities to celebration the Masses beyond sacred places also.